Monocyte chemoattractant protein 1 (MCP-1) released from Helicobacter pylori stimulated gastric epithelial cells induces cyclooxygenase 2 expression and activation in T cells. Issue 9 (11th August 2003) - Futagami, S; Hiratsuka, T; Tatsuguchi, A; Suzuki, K; Kusunoki, M; Shinji, Y; Shinoki, K; Iizumi, T; Akamatsu, T; Nishigaki, H; Wada, K; Miyake, K; et al.
Abstract : Background and aims: To clarify the interaction between gastric epithelial and mucosal T cells, we examined the role of cytokines released from epithelial cells in response to Helicobacter pylori water extract protein (HPWEP) in regulating T cell cyclooxygenase 2 (COX-2) expression and activation. Methods: Media from MKN-28 cells incubated with HPWEP for 48 hours were added to Jurkat T cells and human peripheral T cells. C–C and CXC chemokine concentrations in MKN-28 cell media, and COX-2 expression, interferon γ (IFN-γ), and interleukin (IL)-4 secretions in T cells were determined by western blot analysis and ELISA methods. Distributions of COX-2 positive T cells and monocyte chemoattractant protein 1 (MCP-1) in tissue specimens with H pylori associated gastritis were determined as single or double labelling by immunohistochemistry. Results: MCP-1, IL-7, IL-8, and RANTES were detected in media from MKN-28 cells incubated with HPWEP . Media as a whole, and MCP-1 alone, stimulated COX-2 expression and peripheral T cell proliferation. Anti-MCP-1 antibody inhibited media stimulated COX-2 mRNA expression in Jurkat T cells. Media stimulated IFN-γ but not IL-4 secretion from peripheral T cells, while MCP-1 stimulated IL-4 but not IFN-γ secretion. Both stimulated cytokine release, and peripheral T cell proliferation was partially inhibited by NS-398, a specific COX-2 inhibitor. In mucosa with gastritis, COX-2 was expressed in T cells and MCP-1 was localised mainly in epithelial and mononuclear cells. MCP-1 levels and the intensity of COX-2 expression in tissue samples were closely related. Conclusions: Cytokines such as MCP-1, released from gastric epithelial cells in response to HPWEP, seem to modulate T cell immune responses, at least in part via COX-2 expression.